Additional considerations for gastro-oesophageal reflux disease - A. Marais (South African Family Practice)
Gastro-oesophageal reflux disease (GORD) is a common condition worldwide. It is characterised by numerous upper gastrointestinal tract symptoms, but patients mainly present with heartburn and regurgitation. Various causes have been linked to the pathophysiology of GORD. Some of them are well known, while others are less frequently implicated. Oesophageal inflammation is the result of the inadequately managed suppression of gastric acid caused by the retrograde flow from the stomach through the lower oesophageal sphincter, which may result in complications, including stricture formation, Barrett’s oesophagus, erosive oesophagitis and adenocarcinoma. The incidence per region and country varies significantly, and is dependent on the population demographics. GORD is responsible for an impaired general health score in affected individuals, and has a negative impact on economic productivity in society. Treatment may range from unscheduled self-medication to complicated laparoscopic surgery. This article describes some of the associated factors, revised definitions and the role of surgery in the management of GORD.